Contributions to the design of precast concrete culverts with unusual cross sections - Domingues,Aline Bensi (2021)
Abstract Culverts are structures used in road and railway infrastructure works such as underpasses. Among the several forms of cross-sections, the rectangular one (box culvert) has been mostly employed. However, when installed at high embankments, this structure shows high values of bending moment and shear force, which tend to be amplified by the soil arching. This paper addresses a study of section culvert with an arc cover, called modified, and a section defined by three arches, with a flat base. Such cross-section forms reduce the bending moment due to their geometry, and efforts can be decreased with the use of reduced thicknesses by mechanisms of soil-structure interaction. Analyses were performed in the plane-strain deformation with finite elements towards considering soil-structure interaction, and the results proved the influence of the geometry shape on the soil-culvert interaction behavior. A comparative analysis of the material cost index (ICM) values for 25 geometries (12 modified culverts, 12 culverts defined by three arcs and 1 box culvert) was used for estimating the economic viability of each unusual section culvert. The results showed 27 and 54% economy in materials for modified culvert and culvert defined by three arcs, respectively, in comparison with the rectangular section.